PENGARUH MORALITAS INDIVIDU, EFEKTIFITAS PENGENDALIAN INTERNAL, ASIMETRI INFORMASI, KETAATAN ATURAN AKUNTANSI, DAN PERILAKU TIDAK ETIS TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Sragen) - Riska Nur Rahmah; P. Haryoso (ADVANCE, 2018)
This study aims to provide empirical evidence about the significance the identity of individual morality, the effectiveness of internal control, information asymmetry, compliance with Accounting Fraud Tendencies, and unethical behavior towards the level of fraud in the Regional Work Unit of Sragen Regency. The population in this study is the Regional Work Unit of Sragen Regency. The sample used is 65 respondents. The sampling method is purposive sampling technique. Primary data collected by spreading questioners for respondents. The analytical techniques used in this study are instrument test, classical assumption tests, multiple linear regression analysis and hypothesis test. The results of this study prove that the morality of individuals has positive effect but not as significant as the Accounting Fraud Tendencies. Effectiveness of internal controls has negative and significant effect towards Accounting Fraud Tendencies. Information asymmetry has positive but insignificant towards Accounting Fraud Tendencies. Compliance with Accounting Rules has positive and significant towards Accounting Fraud Tendencies. And unethical behavior has positive and significant effect towards Accounting Fraud Tendencies. R2 Test results showed that Individual Morality, effectiveness of internal control, information asymmetry, compliance with accounting issues, and unethical behavior contributed 51.4% towards Accounting Fraud Tendencies, while the rest 48.6% affected by other variables that not mentioned in this research.Keywords: Effect of Individual Morality, Internal Control Effectiveness, Information Asymmetry, Compliance with Accounting Rules, Unethical Behavior, Accounting Fraud Tendencies.